Analisis Dampak Kebijakan Pemerintah terhadap Daya Saing Tembakau Rakyat di Desa Sukasari Kecamatan Sukasari Kabupaten Sumedang - Syahira, Nur; Noor, Trisna Insan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Tobacco, which is an Indonesian plantation product, has an existence in the eyes of the world. Processed tobacco plants are able to become a major source of foreign exchange for the country. However, according to FAO and UN Comtrade data in 2024, there is a pattern of decreasing tobacco production and the decreasing volume of exports to the world makes this commodity questionable. Based on this background, the two main objectives of this study are: 1) Identifying the competitiveness of smallholder tobacco in Sukasari Village, and 2) Analyzing the impact of government policies by identifying competitiveness between international (social) and private price levels. In this study, the Policy Analysis Matrix (PAM) method was used to analyze competitiveness and policy divergence in tobacco commodities. Samples were taken using a proportional cluster random approach using the Taro Yamane formula. The results showed that tobacco in Sukasari Village has a significant advantage over other products or is competitive. The EPC value is 0.510, NT -Rp59,044,757.3, PC 0.457, and SRP -0.542, which means that the policies issued by the government have not had a positive impact and have not benefited farmers. From the results of the sensitivity analysis, when the rupiah weakens in the eyes of the US dollar by 6 percent is the sensitivity that is most likely to benefit farmers. However, overall, smallholder tobacco in Sukasari Village still has competitiveness.